2016
DOI: 10.1038/nn.4390
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrate of dynamic Bayesian inference in the cerebral cortex

Abstract: Dynamic Bayesian inference allows a system to infer the environmental state under conditions of limited sensory observation. Using a goal-reaching task, we found that posterior parietal cortex (PPC) and adjacent posteromedial cortex (PM) implemented the two fundamental features of dynamic Bayesian inference: prediction of hidden states using an internal state transition model and updating the prediction with new sensory evidence. We optically imaged the activity of neurons in mouse PPC and PM layers 2, 3 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 48 publications
6
64
0
Order By: Relevance
“…Our results are in good agreement with the data from other groups that the zebrafish brain is capable of the predictive coding as those of other higher vertebrates (Attinger et al, 2017;Chao et al, 2018;Funamizu et al, 2016;Makino and Komiyama, 2015;Rao and Ballard, 1999;Schneider et al, 2018;Schwiedrzik and Freiwald, 2017;Sumbre et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in good agreement with the data from other groups that the zebrafish brain is capable of the predictive coding as those of other higher vertebrates (Attinger et al, 2017;Chao et al, 2018;Funamizu et al, 2016;Makino and Komiyama, 2015;Rao and Ballard, 1999;Schneider et al, 2018;Schwiedrzik and Freiwald, 2017;Sumbre et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…For example, some studies have proposed that the stochastic nature of sensory representations provide the means to implicitly encode sensory likelihoods 81,82 . Others have shown that task-related firing rates of single neurons before the presentation of sensory information may be modulated by prior expectations [83][84][85] , and firing rates after the presentation of sensory information may reflect Bayesian estimate of behaviorally-relevant variables 30,[86][87][88] . There have also been attempts to apply reliability-weighted linear updating schemescommonly used in cue combination studies [89][90][91] -to explain how single-neuron firing rates might combine sensory evidence with prior expectations 92,93 .…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous finding that the right but not the left ACC controls observational fear learning in mice (Kim et al, 2012). The brain heavily integrates not only external but also internal causes (Donaldson et al, 2015; Funamizu et al, 2016; Kohl et al, 2018; Larkum, 2013; Lee et al, 2014; R. X. Lee et al, 2015; Matias et al, 2017; Murugan et al, 2017; Remedios et al, 2017; Roome and Kuhn, 2018; Tononi et al, 2016; Zelikowsky et al, 2018).…”
Section: Discussionmentioning
confidence: 99%